1990
DOI: 10.2166/wst.1990.0148
|View full text |Cite
|
Sign up to set email alerts
|

New Trickling Filter Applications in the U.S.A.

Abstract: After falling in disfavor in the U.S. in the 1970s, trickling filters are now reappearing in new applications. The Trickling Filter/Solids Contact (TF/SC) process uses physical and biological flocculation features to transform the poor quality of the trickling filter effluent into an effluent equal to the best activated sludge system. Over 50 TF/SC plants have been built since the process was introduced in 1979. The recent development (1988) of the Biofilm-Controlled Nitrifying Trickling Filter (BCNTF) has per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In pilot-and full-scale NTFs, Parker et al (1986b) cites a 50% increase in average nitrification rates in an NTF over a temperature range of 10-20~ The NTF model just presented, however, predicts only a 15% increase in the maximum rate with temperature. The increased rate of nitrification documented by Parker et al (1989b) is likely not only a result of the decreased activity of the biofilm at lower temperatures, but could also be a function of factors not investigated such as changes in biofilm thickness, wastewater composition (i.e., BOD loads), and media wetting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pilot-and full-scale NTFs, Parker et al (1986b) cites a 50% increase in average nitrification rates in an NTF over a temperature range of 10-20~ The NTF model just presented, however, predicts only a 15% increase in the maximum rate with temperature. The increased rate of nitrification documented by Parker et al (1989b) is likely not only a result of the decreased activity of the biofilm at lower temperatures, but could also be a function of factors not investigated such as changes in biofilm thickness, wastewater composition (i.e., BOD loads), and media wetting.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the overall efficiency of biochemical oxygen demand (BOD) removal can be enhanced when sludges from clarifiers are combined with tower effluent in a trickling filter/solids contact (TF/SC) process (Norris et al 1982). Plastic media towers are also being increasingly used for nitrification of wastewaters (Parker et al 1989b).…”
Section: Introductionmentioning
confidence: 99%
“…Operational stability is important in the case of small treatment plants, this being one of the reasons for the renewed interest in several locations for the "old" trickling filters and biodiscs (rotating biological contactors) for small-sized communities (Upton and Green, 1995). A similar interest to biofilm reactors applied to medium and large communities occurred in developed regions (e.g., USA), after the development of processes combining biomass in suspension with biomass attached to a support medium (Parker et al, 1990). The process advantages renewed the interest for systems with attached biomass, stimulating the development of a great variety of processes.…”
Section: Introductionmentioning
confidence: 97%
“…New ideas based on the development work carried out by Parker and co-workers (Parker, 1989) suggested that instead of combining BOD removal and nitrification in the same biofilm reactor the processes should be separated in order to have a more stable biofilm process for nitrification. The concept of a high rate nitrifying trickling filter (NTF) primarily used for nitrification had recently been demonstrated in pilot scale (Parker et al, 1990).…”
Section: Development Of the High Rate Ntfmentioning
confidence: 99%
“…The concept of a high rate nitrifying trickling filter (NTF) primarily used for nitrification had recently been demonstrated in pilot scale (Parker et al, 1990). This study was oriented to obtaining high nitrification rates not low effluent ammonium levels.…”
Section: Development Of the High Rate Ntfmentioning
confidence: 99%